Lecturer Competence from the Perspective of Undergraduate Psychology Students: A Qualitative Pilot Study - Silvia Di Battista; Monica Pivetti; Giannino Melotti; Chiara Berti (MDPI AG, 2022)
Understanding what students mean by lecturer competence can be crucial in order to recognise indicators with which to assess these competences, improve the quality of university teaching and support lecturers in undertaking their role appropriately. This qualitative pilot study aimed to explore the meaning of competence in a convenience sample of Italian undergraduate psychology students (N = 122). We collected free-associations about what "lecturer competence" actually means for the students. The data corpus underwent a lexical Correspondence Analysis (CA) using the ASPAR procedure of SPAD-T. Two factors were extracted: "socio-emotional dimension" and "task specialist." Students associated the competent lecturer with those who was involved with the achievement of the task goals, on the one hand or those who was engaged in the group's maintenance, on the other. Furthermore, Cluster Analysis identified four clusters: (1) the captivating lecturer; (2) the lecturer oriented to both task and socio-emotional aspects; (3) the rigorous lecturer; and (4) the benevolent lecturer. The preliminary results of this pilot study showed an articulated and multi-dimensional representation of the meanings of lecturer competence from the students' point of view and lay the foundations for a broader quantitative study on the conceptions concerning lecturer competence.